Protein polysaccharide complexes: permanent/nonpermanent interactions between polysaccharides and polypeptides - Gillis, Richard Benjamin (2015)
This investigation looks at the hydrodynamic characterisation of both covalent and non-covalent protein polysaccharide complexes in the context of novel treatments and healthcare. New techniques were employed and evaluated, such as the MUTLTISIG and SEDFIT-MSTAR algorithms for sedimentation equilibrium analysis, as well as the Extended Fujita Approach for sedimentation velocity. Other characterisation techniques were used such as viscometry, density measurement, Dynamic Light Scattering and Size Exclusion Chromatography coupled to Multi Angle Light Scattering. Therapeutics for the treatment of Diabetes Mellitus and Coeliac Disease were considered. There is evidence to suggest that a protein polysaccharide complex extracted from the pulp of pumpkins has a hypoglycaemic effect in human physiology. This extract was assessed in terms of molecular integrity as a precursor to human trial studies. Equally, a novel treatment for Coeliac Disease, gliadin intolerance found in approximately 1% of the population, was assessed in terms of protecting the immune system from gliadin. Well-established methods, along with newly developed methods, were also used to characterise two glycoproteins relevant to the healthcare and food industries: Human gastric mucin, a natural lubricant found in the human stomach, and gum arabic, a plant extract from the Acacia tree. Findings from these investigations were able to add to our current understanding of these two macromolecules.